Localized Abdominal Idiopathic Lipodystrophy - Serrão, V (2008)
Localized loss of subcutaneous tissue can occur after panniculitis, injections of corticosteroids and other drugs, or associated with infectious, autoimmune or neurologic diseases. The "idiopathic lipoatrophies" are a group of poorly characterized diseases, with focal disappearance of subcutaneous fat, and usually the thighs, abdomen or the ankles are affected. Three subtypes have been described based on clinical presentation: lipoatrophia semicircularis, annular lipoatrophy of the ankles and centrifugal lipodystrophy. We describe a 52-year-old female patient who developed a localized atrophy of the abdominal areas over a period of 3 months without any inflammatory signs over the evolution of the disease. The patient denied any previous local trauma or medication of any type. The atrophy stabilized, showing no progression over the last 6 years. The histopathological examination was normal except for the absence of subcutaneous fat, although the biopsy was taken down to the fascia. There was no clinical or serologic evidence of autoimmune diseases and laboratory testing for Borrelia burgdorferi infection was negative. Other causes of localized lipoatrophies were excluded and the final diagnosis was localized idiopathic lipodystrophy. Our patient is the second report on an abdominal lipodystrophy, with no previous inflammatory signs, absence of subcutaneous fat and no associated pathogenic factor. There is no established treatment for idiopathic lipodystrophy, and the lesions do not tend to resolve spontaneously.